Risiko dan return: Analisis Pembentukan Portofolio Saham Berdasarkan Peringkat Diviasi Standar dan beta Periode 2006-2011 - , Chandra Ramdhani Rustam ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The basic principle of financial science states that in an efficient market, investors will get a return of investment that is higher than the average by taking a risk that is higher than average. However, Baker, et al. (2011) in their research on U.S. stocks in the period 1968-2008 found that long-term investments in low-risk stocks will deliver returns above average relatively in the market. The study will look at whether the pattern for realized return is true for the Indonesian stock market. By using standard deviation and beta stocks as risk parameters, this study will compare the return portfolio containing high-risk stocks (High Portfolio) with a portfolio containing low-risk stocks (Portfolio Low) on the Indonesia Stock Exchange during the period from 2006 to 2011. Samples will be taken from stocks LQ-45 during the study period. Statistical tests concluded that the High portfolio has an average return that is not significantly different from Low Portfolio. And even the Low portfolio return performance is consistently better than High Portfolio. This indicates that a portfolio containing high-risk stocks do not necessarily produce a better return than a stock portfolio containing low-risk stocks.